Jacques Rancière and the subject of the rights of man - Sahd, Luiz Felipe (Argumentos - Revista de Filosofia, 2023)
In this article I discuss the proposal to define the subject of human rights in Jacques Rancière's thought. Initially, I examine Rancière's criticism that Arendt depoliticizes human rights due to her Aristotelian presuppositions. Then I explain how Rancière reconceptualizes the relation between the human and the political to understand the politics of human rights in strategic rather than existential terms. I argue that it provides a more adequate basis for understanding human rights politics than is afforded by Arendt’s conception of the political. In this way, Rancière enables us to see contests over human rights as part and parcel of social struggles that are the core of political life since they entail the enactment of equality within conditions of inequality.